2014
DOI: 10.12697/eha.2014.2.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Supporting music students’ refl ection in instrument studies

Abstract: Tänapäevase muusikahariduse valdkonnas rõhutatakse aktiivõppe, sh refleksiooni olulisust. Sellest hoolimata puudub erimetoodika, mis toetaks õppijate refleksiooni pilliõppes. Selle uurimuse tarbeks korraldati ühe Eesti kõrgkooli muusikaõppe üliõpilaste (N = 11) hulgas ekspertide valideeritud refleksiooni toetamise mudeli prooviuuring. Mudel koosnes neljast tsüklist ja baseerus refleksiooni põhiprotsesside (kirjeldamise, hindamise, suhestumise ja refleksiooniprotsessi reflekteerimise) toetamisel. Uurimuse eesmä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recent studies have indicated that in modern music education a new approach to didacticmethodological questions is needed and one of the important developments is active learning and other practical supporting areas (Kivestu & Leijen, 2013;Kivestu, Leijen & Steinbach, 2014;Liimets ja Raudva, 2006;Selke, 2007;Renter-Reintamm, 2009). Since in active learning the acquisition of knowledge is achieved through activities the music teachers in their work should keep in mind that changes should mainly be made in learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that in modern music education a new approach to didacticmethodological questions is needed and one of the important developments is active learning and other practical supporting areas (Kivestu & Leijen, 2013;Kivestu, Leijen & Steinbach, 2014;Liimets ja Raudva, 2006;Selke, 2007;Renter-Reintamm, 2009). Since in active learning the acquisition of knowledge is achieved through activities the music teachers in their work should keep in mind that changes should mainly be made in learning activities.…”
Section: Introductionmentioning
confidence: 99%